2020
DOI: 10.1089/dna.2020.5906
|View full text |Cite
|
Sign up to set email alerts
|

R-Loop Physiology and Pathology: A Brief Review

Abstract: Physiological and pathological roles for R-loop structures continue to be discovered, and studies suggest that R-loops could contribute to human disease. R-loops are nucleic acid structures characterized by a DNA:RNA hybrid and displaced single-stranded DNA that occur in connection with transcription. R-loops form naturally and have been shown to be important for a number of physiological processes such as mitochondrial replication initiation, class switch recombination, DNA repair, modulating DNA topology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 154 publications
(272 reference statements)
0
37
0
Order By: Relevance
“…In all, 49% of proteins (164 of 335) identified in our S9.6 co-IP/MS analysis are known RNA-binding proteins, including several known regulators of R-loop formation, suggesting a high proportion of hits are bona fide R-loop-interacting proteins. R-loops and other non-canonical DNA structures, such as G4s and cruciform DNA, have previously been shown to colocalize throughout the genome 74,75 . We J o u r n a l P r e -p r o o f therefore investigated if R-loop-interacting proteins identified in this study are known to bind to and regulate other DNA or RNA structures.…”
Section: Identification Of R-loop-binding Proteins By Mass Spectrometrymentioning
confidence: 96%
“…In all, 49% of proteins (164 of 335) identified in our S9.6 co-IP/MS analysis are known RNA-binding proteins, including several known regulators of R-loop formation, suggesting a high proportion of hits are bona fide R-loop-interacting proteins. R-loops and other non-canonical DNA structures, such as G4s and cruciform DNA, have previously been shown to colocalize throughout the genome 74,75 . We J o u r n a l P r e -p r o o f therefore investigated if R-loop-interacting proteins identified in this study are known to bind to and regulate other DNA or RNA structures.…”
Section: Identification Of R-loop-binding Proteins By Mass Spectrometrymentioning
confidence: 96%
“…DNA2 possesses both 3' and 5' exonucleolytic activities, and interaction with BLM or WRN helicase can drive its 5' resection activity [8,[19][20][21], consistent with predominately 5' resection providing a source of asymmetry. The zone targeted for mutation coincides with that of the zone that forms an R-loop upon annealing to the 20 bp CRISPR gRNA, which may contribute to mutagenesis as R-loops are inherently unstable [49]. A single-stranded region approximately 20-30 nt in length is protected by a human RPA trimer [17,18], a dimension similar to that of the R-loop.…”
Section: Plos Geneticsmentioning
confidence: 93%
“…R-loops are three-stranded nucleic acid structures consisting of an RNA-DNA hybrid and a misplaced single-strand of DNA (Aguilera & García-Muse, 2012). They typically form during transcription in organisms ranging from yeast to humans (Aguilera & Gomez-Gonzalez, 2017) and play a significant role in normal cellular physiology, being required for the initiation of mitochondrial replication and class switch recombination (Mackay et al, 2020). Moreover, recent studies suggest that R-loops can dynamically regulate gene expression (Niehrs & Luke, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of Top3β is associated with neurological disorders (Mackay et al, 2020) and has been shown to reduce lifespan in mice (Kwan & Wang, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation